Predicting COVID-19 booster intentions among college students using the health belief model: advancing health promotion strategies for uptake - Catalano, Hannah Priest; Christofora, Julianne; Richards, Keith; Hyatt Hawkins Shaw, Katherine; Kiser, Kevin (Frontiers in Public Health, 2024)
Background: COVID-19 remains a significant public health threat. The primary purpose of this study was to test the health belief model (HBM) constructs in predicting COVID-19 booster intentions of college students. Methods: A total of 285 students enrolled at large public university in the Southeastern U.S., who were 18 years and older, completed an online survey to assess COVID-19 vaccination status, prior or current COVID-19 infection, demographics, and HBM constructs. Results: Over three quarters of the sample (81.4%, n = 232) was fully vaccinated, 2.1% (n=6) was partially vaccinated, and 16.5% (n = 47) was unvaccinated. Furthermore, 53.4% (n = 124) of students who self-reported being fully vaccinated also reported receiving the booster vaccine. Nearly half of the sample (49.1%, n = 140) self-reported previously or currently testing positive for COVID-19. Results of the stepwise multiple regression indicated the HBM constructs of perceived benefits (β =.596; p<.001) and cues to action (β =.275; p<.001) were significant predictors of respondents' behavioral intention to receive the COVID-19 booster in the next 6 months. The significant predictors at step 2 accounted for 64.6% (R 2 = .646, F (2, 111 = 101.331, p<.001) of the variance in behavioral intention to get the COVID-19 booster in the next 6 months. Conclusion: Practitioners developing HBM-based interventions to enhance COVID-19 booster intentions among college students should tailor health promotion strategies that target perceived benefits and cues to action. Although some of the HBM constructs were not statistically significant in the prediction model, they should not be entirely discounted in health promotion practice. Instead, practitioners should focus on supplemental strategies to improve those domains in college students.